The effects of prolonged simulated soccer match-play on dominant and non-dominant knee and hip extension angles during side-cutting maneuvers / Muhammad Hamdan - Hamdan, Muhammad (2017)
This study aimed to investigate the changes of the sagittal plane knee and hip extension angles following prolonged exertion from extra time during overground simulated soccer match-play using a two dimensional motion analysis system. In the first and second part of this study, a comparison of motion analysis system was compared for criterion validity by testing them inter-software, inter- and intra- tester using two-way random effects, single measures intraclass correlation coefficients (ICC2,1). All, ICC2,1 values for the knees and hips showed close to perfect scores thus supporting the utility of a two dimensional motion analysis system using an open-source, free software.